-2z-9=-2z-10+1

Simple and best practice solution for -2z-9=-2z-10+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2z-9=-2z-10+1 equation:


Simplifying
-2z + -9 = -2z + -10 + 1

Reorder the terms:
-9 + -2z = -2z + -10 + 1

Reorder the terms:
-9 + -2z = -10 + 1 + -2z

Combine like terms: -10 + 1 = -9
-9 + -2z = -9 + -2z

Add '9' to each side of the equation.
-9 + 9 + -2z = -9 + 9 + -2z

Combine like terms: -9 + 9 = 0
0 + -2z = -9 + 9 + -2z
-2z = -9 + 9 + -2z

Combine like terms: -9 + 9 = 0
-2z = 0 + -2z
-2z = -2z

Add '2z' to each side of the equation.
-2z + 2z = -2z + 2z

Combine like terms: -2z + 2z = 0
0 = -2z + 2z

Combine like terms: -2z + 2z = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 6t-9=3(2t-4)+3 | | 4x+2(4+x)=3(2+5x) | | 618.5172=2*3.14*24.01+2*3.14*4.9*h | | 3.6x-1.2=.7(10-x) | | 6.5(1+0.495x)=5.114+4.3x | | 19694.08=2*3.14*196+2*3.14*14*h | | .3x=1.2+2.3x | | 64d^5-32d^2= | | 6x+1.5=4x-3 | | 0.4(x-10)+0.6x=1 | | Y+(3-5)=12 | | (5z+3)(8+z)=0 | | 7sec(x)=7 | | 33.33t=-.25 | | -16-3c=5c | | 8343.8592=2*3.14*17.64+2*3.14*4.2*h | | -15n+8n+34-4=-65 | | 0.3z-62.1=3z | | -.1a=0 | | 15n+8n+34-4=-65 | | 6x-8x+5=-2x+-4+7 | | 1965.7656=2*3.14*54.76+2*3.14*7.4*h | | 15q+13q+8q=180 | | 3y=5-2y | | 3x+63+66=180 | | 20t+5t+5t=180 | | 3t+69+78=180 | | 1.4t+2.7=5.5 | | -25.294-0.8*-4.6=-3.2+2.7(2.7*-4.6+5.6) | | -8x-3=37 | | -25.294-0.8*4.6=-3.2+2.7(2.7*4.6+5.6) | | .5(x-1)=.33(x+1) |

Equations solver categories